The Importance of Human Resources in Management Development (A literature Review) - Alami, Reza; Fattahi, Majid (IJRDO - Journal of Applied Management Science, 2018)
Today, the role and importance of human resources in the process of production and delivery of services in human societies is recognized as a main factor and is evident in industrial, economic, and service organizations and firms. Human resource management is one of the necessary needs of today’s business. Human resource management department has a very important role for supply of the human being to main resources of companies. Human resource management department has fundamental role for personnel recruiting, orientation and performance appraisal and so on. Human resource management issues to be addressed at the highest level in the organization and management of strategic decisions are required. The purpose of current paper is based on a review of 43 refereed article and dissertation that focused on human resource management, scope and affecting factors on human resource management, human resource management functions and relationship between organizational effectiveness and human resources management.